(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Khairullah AR, Sudjarwo SA, Effendi MH, Ramandininto SC, Gelolodo MA, Widodo A, Riwu KHP, Kurniawati DA, Rehman S. 2022. Profile of Multidrug Resistance and Methicillin-Resistant Staphylococcus aureus (MRSA) on dairy cows and risk factors from farmer. Biodiversitas 23: 2853-2858. Staphylococcus aureus is a facultative anaerobic Gram-positive coccus that causes mastitis and is one of the most widespread pathogenic bacteria in dairy farming. These bacteria can quickly develop into antibiotic-resistant strains due to inappropriate antibiotic administration. Staphylococcus aureus bacteria that have Multidrug-Resistant (MDR) properties can be known as Methicillin-Resistant S. aureus (MRSA) if these bacteria are resistant to beta-lactam antibiotics. The high number of MDR and MRSA contamination in dairy farms as a result of excessive administration of antibiotics in the treatment of dairy cows and the spread of these bacteria cannot be separated from the sanitation management at the time of milking, it can be from milk that is milked from the udder and it can also be from the hands of farmers during the milking process. This study tests antibiotic resistance and detects Methicillin-Resistant S. aureus (MRSA) strains sourced from milk and hand swabs of farmers in Probolinggo, East Java, Indonesia. A total of 109 dairy cow’s milk samples and 41 samples of farmers’ hand swabs were taken from each farm. Samples were cultured and purified using Mannitol Salt Agar (MSA). Staphylococcus aureus resistance profile was performed by disk diffusion test using antibiotic disks such as Oxacillin, Cefoxitin, Tetracycline, Erythromycin, and Gentamicin. Staphylococcus aureus isolates that were resistant to Oxacillin and Cefoxitin antibiotics were then tested for Oxacillin Resistance Screening Agar Base (ORSAB) as a confirmation test for Methicillin-Resistant S. aureus (MRSA). The results of the isolation and identification found 80 (53.33%) S. aureus isolates, then the results of the resistance test found 8 (10%) S. aureus isolates that were Multidrug-Resistant (MDR), and in the Oxacillin Resistance Screening Agar Base (ORSAB) test there were 3 isolates of S. aureus MDR were ORSAB positive. It can be found that there are several S. aureus isolates that are Multidrug-Resistant (MDR) and Methicillin-Resistant S. aureus (MRSA) in dairy farms. The S. aureus that is MDR and MRSA can be spread to the community and will endanger public health. Thus, prevention and control measures are needed to suppress the spread of S. aureus infection on a dairy farm in Probolinggo, East Java, Indonesia.